Burden and Life Satisfaction among Caregivers of Hemodialysis Patients Residing in Kathmandu - Mankeshari Maharjan; Ajita Silwal; Bebita Adhikari; Bandana Thapa; Bhagawati Bhandari; Sangita Shrestha (Journal of Karnali Academy of Health Sciences, 2021)
Introduction: The patients undergoing hemodialysis need long-term care. Caregivers of hemodialysis patients can suffer from physical and psychological stress that can affect the level of burden and life satisfaction among them. The objective of the study was to assess burden and the life satisfaction among caregivers of hemodialysis patients.